Combination of Pulai Leaf (Alstonia scholaris (L.) R. Br.) and Papaya Leaf (Carica papaya L.) Water Extract as HMG-CoA Reductase Inhibitor - Sulistiyani; Andrianto, Dimas; Mariati, Sri (Current Biochemistry, 2024)
Heart disease has become the leading cause of death in the world in the last 15 years. This disease has several primary risk factors, one of which is hypercholesterolemia. Cholesterol biosynthesis in the liver is influenced by the activity of the rate-limiting enzyme, HMG-CoA reductase. Traditional herbal medicine provides alternative treatment for hypercholesterolemia. Both pulai and papaya leaves were reported as HMG-CoA reductase inhibitors. There has been very limited study however, on the efficacy of a mixture of aqueous extracts of the two in inhibiting HMG-CoA reductase. This study aims to determine the activity of a mixture of water extracts of both pulai and papaya leaves. The activity of the enzyme HMG-CoA reductase was measured by Abcam® kit No. Ab204701 by spectrophotometric method at 334 nm. The results showed that the three extracts of the combination of pulai and papaya leaves had four times better inhibitory action than the single extract (p0.05). The results of the phytochemical literature study showed that the aqueous extract contained flavonoids, alkaloids, tannins, and saponins